COMPARING THE FREQUENCY OF MANIFESTATION OF HYPERDONTIA AND HYPODONTIA - Greta Yordanova; Mario Grancharov (Peytchinski Publishing, 2023)
Introduction: Hypodontia and hyperdontia are two dental phenomena with deviations in the number of teeth - reduction and increase of tooth germs. The aim of the study is to compare the frequency of manifestation of hyperdontia and hypodontia, their distribution by tooth groups among Bulgarian orthodontic patients. Materials and methods: The prospective clinical-epidemiological study covered 2676 patients: 1705 (63.7%) female and 971 (36.3%) male. They were detected and diagnostically proven with supernumerary and missing teeth. The findings were distributed according to their localization to make a comparative analysis. Results: The patients established with hypodontia were 5.79% with average age of 15.17±5.34 years, and hyperdontia in 3.13% of patients with average age of 11.80±4.65 years. Statistically credible, hyperdontia was more frequently observed in males, while hypodontia was significantly more frequently observed in females. The hypodontia was the most commonly observed in the mandibular distal segment - second premolars (46.5%), next affected was the maxillary lateral (37.4%), followed by the maxillary distal segment (32.3%), and the least was the mandibular frontal segment (12.9%). The supernumerary teeth found in the maxillary frontal segment were incisors and mesiodens (91%) compared to the maxillary distal segment (9%) was significant. In the mandible, the difference between the frontal (42.3%) and distal segment (57.7%) was without statistical significance. Conclusions: Knowledge of the clinical characteristics of hypodontia and hyperdontia are important for targeted early diagnosis and treatment. Both of these specific problems have an effect on an individual's function and psychosocial well-being.